Long-term health-related quality of life after McKeown and Ivor Lewis esophagectomy for esophageal carcinoma. Issue 11 (23rd May 2020) - Jezerskyte, E; Saadeh, L M; Hagens, E R C; Sprangers, M A G; Noteboom, L; van Laarhoven, H W M; Eshuis, W J; Hulshof, M C C M; van Berge Henegouwen, M I; Gisbertz, S S
Summary: Introduction: Both cervical (McKeown) and intrathoracic (Ivor Lewis) anastomosis of transthoracic esophagectomy are surgical procedures that can be performed for distal esophageal or gastro-esophageal junction (GEJ) cancer. The purpose of this study was to investigate the long-term health-related quality of life (HR-QoL) after McKeown and Ivor Lewis esophagectomy in a tertiary referral center. Methods: Disease-free patients >1 year following a McKeown or an Ivor Lewis esophagectomy with a two-field lymphadenectomy for a distal or GEJ carcinoma visiting the outpatient clinic between 2014 and 2018 were asked to complete the EORTC QLQ-C30 and EORTC QLQ-OG25 questionnaires. HR-QoL was investigated in both groups. Results: A total of 89 patients were included after McKeown and 115 after Ivor Lewis esophagectomy. Median follow-up was 2.4 years (IQR 1.7–3.6). Patients after McKeown esophagectomy reported more problems with 'eating with others' compared to patients after Ivor Lewis esophagectomy (mean scores: 49.9 vs. 38.8). This difference was both clinically relevant and significant after correction for multiple testing (β = 11.1, 95% CI 3.105–19.127, P  = 0.042). Patients in both groups reported a poorer HR-QoL (≥10 points) than the general population with respect to nausea and vomiting, dyspnea, appetite loss, financial difficulties, problems with eating, reflux, eating with others, choked when swallowing, trouble with coughing, and weight loss. Conclusion: Long-term HR-QoL of disease-free patients following a McKeown or Ivor Lewis esophagectomy for a distal or GEJ carcinoma is largely comparable. Irrespective of the surgical technique, patients' HR-QoL following esophagectomy is compromised. When given the choice, patients should be informed that after a McKeown esophagectomy more problems while eating with others can occur.